Texture mapping for 3D craniofacial surface model: preliminary results - Abd. Majid, Zakiah; Setan, Halim; Majid, Zulkepli; Chong, Albert K.; Ahmad, Anuar (2004)
This research focuses on texture mapping (a powerful technique for adding realism to a computer-generated scene) for craniofacial applications. In its basic form, texture mapping lays an image onto an object in a scene. The texture mapping is important for 3D craniofacial data to help identify landmark in measurement process. Two close range measurement methods are used for data capture, i.e. laser scanning and digital photogrammetry. The process of texture mapping consists of 2 steps. Firstly, a human face is scanned from two laser scanners. At the same time, an image of the human face (from the front side) is taken using normal digital camera to capture the 2D texture. Secondly, the 2D image is draped onto the 3D laser scan data (using RapidForm software) to generate a 3D texture image. Some preliminary results are shown to illustrate this approach. For complete texture mapping, we plan to use multiple digital cameras (for different sides of the face) operating simultaneously, for generating a complete 3D image of a face. The 3D image will be draped onto the 3D laser scanned image.